2022
DOI: 10.3390/su142215433
|View full text |Cite
|
Sign up to set email alerts
|

Food Insufficiency among Job-Loss Households during the Pandemic: The Role of Food Assistance Programs

Abstract: During the early stages of the pandemic, many households experienced a loss of employment income, which worsened food insecurity and food insufficiency across the United States. This study aimed to examine whether food assistance programs (FAPs) significantly alleviated food insufficiency (FI) among job-loss households during the pandemic. The analysis was conducted with nationally representative survey data (n = 229,668) collected across 50 states and D.C. in 2020. Spatial analysis and logistic regression wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Social disparities in FI persist in the United States (Li et al 2022). Higher rates of FI have been observed among students from underrepresented and marginalized backgrounds, students with disabilities, students with children, and students who identify as pansexual, queer, bisexual, gay or lesbian, transgender, or nonbinary (Adamovic et al 2022;Soria et al 2020).…”
Section: Review Of the Relevant Literature Published In The United St...mentioning
confidence: 99%
See 1 more Smart Citation
“…Social disparities in FI persist in the United States (Li et al 2022). Higher rates of FI have been observed among students from underrepresented and marginalized backgrounds, students with disabilities, students with children, and students who identify as pansexual, queer, bisexual, gay or lesbian, transgender, or nonbinary (Adamovic et al 2022;Soria et al 2020).…”
Section: Review Of the Relevant Literature Published In The United St...mentioning
confidence: 99%
“…There is still much to learn about social disparities in FI among university students and the potential risk factors in the background of the COVID-19 pandemic (Jehi et al 2022). Furthermore, during the pandemic, it has become increasingly challenging to provide food assistance for university students due to campus closures, the implementation of physical distancing policies, and various consequences caused by the global pandemic (Blackmon et al 2021;Esobi et al 2021;Li et al 2022;Ahmed et al 2023). However, little is known about the relationship between students' utilization of FAPs and their FI, particularly among socially vulnerable students.…”
Section: Research Gaps and Objectivesmentioning
confidence: 99%
“…The PRISMA ow diagram is shown in Fig.1. Two-third of eligible studies used a survey study design(17, 19, 22, 28, 29, 32-34, 36, 38, 43-47, 50-54, 57, 59, 61, 63-67); others included quasi-experiment(25,41), simulation(20,22,27,55, 60, 69), observational(26, 38,49, 56), and randomized control trial design(42, 48, 58, 62).We identi ed 28 unique individual-level economic relief programs among eligible studies and categorized them into seven groups.Of the 50 eligible studies, three sets of seven studies reported on COVID-19 related unemployment assistance programs (18,19,22,23, 26,30,47), COVID-19 food assistance programs(22,24, 28,40,43,44, 46), and expanded paid sick leave (16,25, 34-36, 39, 49) in the context of COVID-19 pandemic and In uenza epidemic. Eleven eligible studies reported on COVID-19 cash transfer programs(17,20,45, 48,50,52,54, 56, 58, 68, 69); nine studies evaluated vaccine and…”
mentioning
confidence: 99%